Rheology methods as a tool to study the impact of whey powder on the dough and breadmaking performance of wheat flour - Macedo, Christine (2020)
Considering the nutritional value, whey is an excellent ingredient for the development of food products, in line with the concept of a circular economy for the reuse of industry by-products. The main objective of this work was to evaluate the impact of the whey addition on the rheology of wheat flour dough and breadmaking performance, using both empirical and fundamental methods. Di erent levels of commercial whey powder (0%, 12%, 16% and 20% w/w) were tested in a bread formulation previously optimized. Dough mixing tests were performed using Micro-doughLab and Consistograph equipment, to determine the water absorptions of di erent formulations and evaluate empirical rheology parameters related to mixing tolerances. Biaxial extension was applied by the Alveograph to simulate fermentation during the baking process. Fermented doughs were characterized in a Texturometer using penetration and extensibility tests, and by small amplitude oscillatory shear (SAOS) measurements, a fundamental rheology method, in a Rheometer applying frequency sweeps. Loaf volume and firmness were used to study the breadmaking quality. Despite a negative impact on the empirical rheology parameters of the dough and poorer baking results, the use of this by-product should be considered for nutritional and sustainability reasons. In addition, significant correlations (r2 > 0.60) between the dough rheology parameters obtained from the empirical measurements were established. Changes in the gluten structure were not accurately detected by the SAOS measurements and Texture Profile Analysis of the doughs, and a correlation between fundamental and empirical measurements was not found. Consistograph or Micro-doughLab devices can be used to estimate bread firmness. Extensional tests in the Texturometer, using SMS/Kie er Dough and Gluten Extensibility Rig, may predict loaf volume